Fault Location on Series Compensated Power Transmission Lines Using Transient Spectrum - R. Jayamurthi, C; Sowmiya, A (International Journal of Engineering and Technology, 2018)
A Transmission line fault locality analyzing process for multi-circuit power transmission series compensated line up with phasor records as of smart electronic devices available at both split ends. During the case of unavailability of synchronize records, logical synchronization is acquire by means of an operative. During the power transmission process, the techniques consider untransposed line segment ensuing on top of two side of the power fault with the dispersed environment of transmission line. In favor of in the pink phase, current on two sides flow at the fault position be identical unlike exceptional current on two sides in a fault phase. This be checkered in excess of the line length along with the fault location is identify. The technique does not need the model of the series recompense located by at all locality on the line along with be capable of be use for both internal and external-circuit fault. It as well reflects on reactive element of the fault impedance for accurate fault position. The technique is analyzed with PSCAD/EMTDC simulation used for a multi-circuit series-compensated line in Indian smart power grid. Estimation revise confirm the strength of the technique used for different faults.Â